2009
DOI: 10.1007/s11738-009-0418-9
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and glutathione disulfide affect adventitious root formation and growth in tomato seedling cuttings

Abstract: To study the relationship between glutathione and rooting, tomato seedling cuttings, grown on basal-or on auxin-supplemented media, were treated with the reduced (GSH) or oxidized (GSSG) form of this antioxidant. In turn, the consequences of the depletion of GSH pool on rooting were tested using L-buthionine sulfoximine (BSO), a specific inhibitor of GSH biosynthesis. Effects of the aforementioned treatments on rooting response were assessed. GSH treatment promoted root formation on cuttings grown on both basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…The stimulation in glutathione level in auxin-treated plant is supported by Takahashi and Nagata (1992) indicating that a significant increase in glutathione level and glutathione Stransferase activity was detected in tobacco mesophyll protoplasts. The level of glutathione was also increased in roots of tomato seedlings after IAA treatment indicating that auxin may regulate root elongation through regulation of glutathione content (Tyburski and Tretyn 2010). Moreover, auxins enhanced the capacity for glutathione synthesis in C. vulgaris when there is no demand for this substance in our experimental system.…”
Section: Discussionmentioning
confidence: 55%
“…The stimulation in glutathione level in auxin-treated plant is supported by Takahashi and Nagata (1992) indicating that a significant increase in glutathione level and glutathione Stransferase activity was detected in tobacco mesophyll protoplasts. The level of glutathione was also increased in roots of tomato seedlings after IAA treatment indicating that auxin may regulate root elongation through regulation of glutathione content (Tyburski and Tretyn 2010). Moreover, auxins enhanced the capacity for glutathione synthesis in C. vulgaris when there is no demand for this substance in our experimental system.…”
Section: Discussionmentioning
confidence: 55%
“…1; Table 1). Previously Tyburski and Tretyn (2010b) have indicated that GSH enhances roots formation. They have stated, however, that only an optimal concentration of GSH in meristematic parts of growing roots is effective in stimulation of root growth.…”
Section: Gsh and Aa Affect Rhizogenesis In Opposite Mannermentioning
confidence: 97%
“…Since GSH is involved in ROS detoxification (Noctor and Foyer 1998) it can be considered as an important factor regulating an optimal ROS level in growing root hairs. It has to be noted that auxin treatment might increase endogenous GSH concentration to the supraoptimal level (Tyburski and Tretyn 2010b) leading to the deceleration of root hairs growth.…”
Section: Gsh and Aa Affect Rhizogenesis In Opposite Mannermentioning
confidence: 99%
“…For example, a positive effect of exogenous addition of a mix of three (Serine/Alanine/Glycine) or two (Serine/Alanine) amino acids on wheat root tolerance of oxygen deprivation was detected [19] . Reduced glutathione treatment promoted tomato seedling cuttings root formation [15] . Our experiment on the ornamental plants of C. camphora showed that the lower concentration of BSA is beneficial to the cuttings survived in adverse environments, and to the new roots formed as soon as possible.…”
Section: Discussionmentioning
confidence: 98%
“…Plants grown in different N mixtures were similar in size, but those supplied with organic N displayed a significantly greater root fraction [14] . Reduced glutathione treatment promoted root formation in cuttings grown on both base-and auxin-supplemented media [15] . Under controlled environmental conditions, plant uptake of organic and inorganic N forms in the dominant desert shrub Larrea tridentata was quantified to assess the potential effects of elevated atmospheric CO 2 on plant N uptake dynamics [16] .…”
Section: Introductionmentioning
confidence: 98%